Analisis Isi Novel “Laut Bercerita” dalam Bingkai Ekofeminisme - Azida, Mafriha; Fitri, Alifa Nur (Jurnal Ilmu Komunikasi, 2021)
Ecological criticism is mostly understood as the study of literature with an ecological perspective. The novel "Laut Bercerita" by Leila Salikha Chudori builds a relationship between women and the preservation of nature and the environment. This novel is a literary genre that deconstructs ecofeminism or green literature. The purpose of this study was to increase knowledge about the relationship between literary works and the thought of the ecofeminism movement in the novel "Laut Bercerita". This research method uses qualitative content analysis. The results show that the importance of conserving nature and risking their property, life, and family to achieve prosperity and justice for the community. Human dependence on nature must also be harmonized with the maintenance and preservation of nature. The novel “Laut Bercerita” offers a new perspective on the relationship between humans and nature. The preservation of nature and the environment is shown by the struggle of Kinan and his friends